Contaminant Biotransport by Pacific Salmon in the Great Lakes - Gerig, Brandon S.; Janetski, David J.; Chaloner, Dominic T.; Lamberti, Gary A. (Frontiers in Ecology and Evolution, 2020)
In the Laurentian Great Lakes, introduced Pacific salmon (Oncorhynchus spp.) deposit resources and contaminants as carcass and gametic tissue during spawning migrations to tributaries. Such ecosystem linkages can increase growth and contaminant bioaccumulation in stream-resident fish but mechanisms driving this process remain unclear. In this mini-review, we synthesize findings from observational, experimental, and modeling studies related to Pacific salmon contaminant biotransport in the Great Lakes. First, contaminant biotransport varies among Great Lakes basins suggesting that basin-level characteristics including salmon abundance and historic contamination are important factors controlling the movement of contaminants from the lakes to tributaries. Second, stream-resident fish exposed to salmon have 24-fold higher PCB but moderately lower Hg concentrations when compared to locations without salmon. This finding is explained by differential bioaccumulation of PCB and Hg into different tissue types; analysis of salmon tissue indicates that eggs have elevated PCB and lower Hg than carcasses. Third, stream-resident fish exhibit a dietary shift and increased ration reflecting salmon egg consumption. Last, models suggest that salmon egg consumption can drive a trade-off between PCB and Hg bioaccumulation. This review identifies mechanisms controlling the transfer of salmon-derived energy potential strategies for management. Future research should be directed at identifying other biovectors and determining a list of emerging contaminants that could be subject to biotransport.